2017
DOI: 10.1002/app.44953
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of amino silane functional montmorillonite on intumescent flame‐retarded SEBS and its mechanism

Abstract: A functional modified montmorillonite (F-OMMT) was prepared by intercalating pristine montmorillonite using phosphonium salt and subsequent grafting through alkyl amino silane coupling. The synergistic effect of F-OMMT on the flame retardancy and char-forming mechanism of intumescent flame-retarded polystyrene-b-(ethylene-co-butylene)-b-styrene (SEBS) composite (SEBS/IFR) was investigated. When 2 wt % F-OMMT was introduced to the SEBS/IFR composite, the limited oxygen index (LOI) value of the composite increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The increase is mainly owed to the excellent char‐formation ability of MCAPP and MF resin, as well as the char‐forming reaction between APP and MF resin . The formed char layer, which has excellent thermal stability and barrier property, can isolate the transfer of heat and mass from the polymer to the heat source and prevent the substrate materials from further breaking in a fire . All these results indicate that MCAPP is feasible for improving the flame retardancy of EPS foam.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The increase is mainly owed to the excellent char‐formation ability of MCAPP and MF resin, as well as the char‐forming reaction between APP and MF resin . The formed char layer, which has excellent thermal stability and barrier property, can isolate the transfer of heat and mass from the polymer to the heat source and prevent the substrate materials from further breaking in a fire . All these results indicate that MCAPP is feasible for improving the flame retardancy of EPS foam.…”
Section: Resultsmentioning
confidence: 95%
“…The problem of smoke release has been brought to the world's attention now as the dominant reason for serious casualties in a fire . It is necessary to achieve smoke suppression during combustion, especially for building materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, SEBS can be easily processed and modified. Due to the compatibility, it is widely used in hybridization with many different types of polymers such as copolymer coatings, adhesives, sealants, and engineering plastics . In addition, scientific studies have shown that increased concentration of SEBS in hybrid polymer blends could improve breaking elongation and interfacial adhesion, which allows developing the properties of ductility, toughness, and impact‐resistance …”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from its structural properties, PGS has drawn emerging interest as a potential alternative to conventional sorbents . As for other applications of clay‐based materials, sepiolite, montmorillonite, and hydrotalcite can be used as flame retardant to improve flame retardance of the polymers dramatically. As one of the core candidates, the flame retardancy applications of PGS were also well considered .…”
Section: Introductionmentioning
confidence: 99%